Complex training in ice hockey: the effects of a heavy resisted sprint on subsequent ice-hockey sprint performance - Matthwes, M. J.; Comfort, P.; Crebin, R. (The Journal of Strength and Conditioning Research, 2010)
The aim of the study was to investigate the acute effect of a heavy resisted sprint when used as a preload exercise to enhance subsequent 25-m on-ice sprint performance. Eleven competitive ice-hockey players (mean ± SD: Age = 22.09 ± 3.05 years; Body Mass = 83.47 ± 11.7 kg; Height = 1.794 ± 0.060 m) from the English National League participated in a same-subject repeated-measures design, involving 2 experimental conditions. During condition 1, participants performed a 10-second heavy resisted sprint on ice. Condition 2 was a control, where participants rested. An electronically timed 25-m sprint on ice was performed before and 4 minutes after each condition. The results indicated no significant difference (p = 0.176) between pre (3.940 + 0.258 seconds) and post (3.954 + 0.261 seconds) sprint times in the control condition. The intervention condition, however, demonstrated a significant 2.6% decrease in times (p = 0.02) between pre (3.950 + 0.251 seconds) and post (3.859 + 0.288 seconds) test sprints. There was also a significant change (p = 0.002) when compared to the times of the control condition. These findings appear to suggest that the intensity and duration of a single resisted sprint in this study are sufficient to induce an acute (after 4 minutes of rest) improvement in 25-m sprint performance on ice. For those athletes wishing to improve skating speed, heavy resisted sprints on ice may provide a biomechanically suitable exercise for inducing potentiation before speed training drills.